Identification of ACKR4 as an immune checkpoint in pulmonary arterial hypertension - Jiang, Chen-Yu; Wu, Li-Wei; Liu, Yi-Wei; Feng, Bei; Ye, Lin-Cai; Huang, Xu; He, Yang-Yang; Shen, Yi; Zhu, Yi-Fan; Zhou, Xing-Liang; Jiang, Dai-Ji; Qi, Hai-Kun; et al. (Frontiers in Immunology, 2023)
Objective: Inflammation is recognized as a contributor in the development of pulmonary arterial hypertension (PAH), and the recruitment and functional capacity of immune cells are well-orchestrated by chemokines and their receptors. This study is aimed at identification of critical chemokines in the progression of PAH via transcriptomic analysis. Methods: Differentially expressed genes (DEGs) from lungs of PAH patients were achieved compared to controls based on Gene Expression Omnibus (GEO) database. Gene set enrichment analysis (GSEA) was applied for functional annotation and pathway enrichement. The abundance of immune cells was estimated by the xCell algorithm. Weighted correlation network analysis (WGCNA) was used to construct a gene expression network, based on which a diagnostic model was generated to determine its accuracy to distinguish PAH from control subjects. Target genes were then validated in lung of hypoxia-induce pulmonary hypertension (PH) mouse model. Results: ACKR4 (atypical chemokine receptor 4) was downregulated in PAH lung tissues in multiple datasets. PAH relevant biological functions and pathways were enriched in patients with low-ACKR4 level according to GSEA enrichment analysis. Immuno-infiltration analysis revealed a negative correlation of activated dendritic cells, Th1 and macrophage infiltration with ACKR4 expression. Three gene modules were associated with PAH via WGCNA analysis, and a model for PAH diagnosis was generated using CXCL12, COL18A1 and TSHZ2, all of which correlated with ACKR4. The ACKR4 expression was also downregulated in lung tissues of our experimental PH mice compared to that of controls. Conclusions: The reduction of ACKR4 in lung tissues of human PAH based on transcriptomic data is consistent with the alteration observed in our rodent PH. The correlation with immune cell infiltration and functional annotation indicated that ACKR4 might serve as a protective immune checkpoint for PAH.